Answer:
f(g(-64)) = -190
Step-by-step explanation:
The functions are not well written.
Let us assume;
f(x) = x+1
g(x) = 3x+1
f(g(x)) = f(3x+1)
Replace x with 3x+1 in f(x)
f(g(x)) = (3x+1) + 1
f(g(x)) = 3x + 2
f(g(-64)) = 3(-64) + 2
f(g(-64)) = -192+2
f(g(-64)) = -190
<em>Note that the functions are assumed but same method can be employed when calculating composite functions</em>
Answer:
10 ft cubed
Step-by-step explanation:
The volume of a pyramid is 1/3 the volume of a prism with the same base area & height.
30/3=10
Answer: 3/4 I’m pretty sure. I looked at it and got confused so not 100% sure.
Answer:
The answer is 19305
Step-by-step explanation: